(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
This study deals with spatial and temporal distributions of organic and inorganic phosphorus in sedimentary columns from Al-Kabir Al-Shimaliand Al-Hussain estuaries, during the period March 2013- February 2014. Organic phosphorus concentrations ranged between (2.0 - 207.6) µg/gin sediments from Al-Kabir Al-Shimali estuary, and from (1.7 –130.9) µg/gin sediments from Al-Hussainestuary. Sediment content from inorganic phosphorus ranged between (12.4 – 371.2)μg / g at sediments from Al-Kabir Al-Shimali estuary, and from (2.0 - 242.6)μg /g at Al-Hussain estuary. Granular composition of sediments did not play a significant role in the temporal and spatial distributions of organic and inorganic phosphorus. In general, organic and inorganic phosphorus concentrations decreased gradually from winter to summer, and from surface layers of the sedimentary column towards the deeper layers. The ratiobetween inorganic and organic phosphorus increasedfrom river into marine sediments. In addition, this ratio increased gradually as the sedimentdepthincreased, and was high in winter and low in summer. تتناول هذه الدراسة التوزع المكاني والزماني للفوسفور العضوي واللاعضوي في العمود الرسوبي لمنطقة مصبي نهر الكبير الشمالي ونهر الحصين خلال الفترة الممتدة من آذار2013 ولغاية شباط 2014. تراوح تركيز الفوسفور العضوي بينµg/g ((2.0 - 207.6في رسوبيات مصب نهر الكبير الشمالي، وبين µg/g (130.9-1.7 ) في رسوبيات مصب نهر الحصين، بينما تراوح محتوى الرسوبيات من الفوسفور اللاعضوي بين12.4- 371.2 )µg/g) في مصب نهر الكبير الشمالي، وبين242.6µg/g)- 2.0) في مصب نهر الحصين. لم يلعب التركيب الحبيبي للرسوبيات دوراً ملحوظاً في التوزع الزماني والمكاني للفوسفور العضوي واللاعضوي. تدرج بشكل عام تركيز الفوسفور العضوي واللاعضوي في الانخفاض بدأ من الشتاء إلى الصيف من جهة، وبالانتقال في عمق العمود الرسوبي من جهة أخرى. ازدادت نسبة الفوسفور اللاعضوي إلى الفوسفور العضوي في الرسوبيات المدروسة بالانتقال من المياه النهرية إلى المياه البحرية، كما ازدادت هذه النسبة تدريجياً مع ازدياد عمق الرسوبيات. كانت هذه النسبة أيضاً مرتفعة في فصل الشتاء ومنخفضة في فصل الصيف.